Comparative analysis of H2-diesel co-combustion in a single cylinder engine and a chassis dynamometer vehicle. (8th January 2019) - Talibi, Midhat; Hellier, Paul; Watkinson, Martin; Ladommatos, Nicos
Abstract: Concerns as to the adverse effects of diesel engine exhaust on urban air quality have resulted in increasingly stringent emissions legislation, with the prospect of many major global cities potentially banning diesel vehicles. Emissions of nitrogen oxides (NOx ) and particulate matter (PM) are linked to increases in premature mortality, and the simultaneous control of both pollutants through modified combustion strategies presents a significant challenge. In this work, the effects of displacing diesel fuel with hydrogen on exhaust emissions were investigated in both a single cylinder research engine and in a demonstration vehicle. In the initial stage, tests were undertaken on a supercharged, direct injection, single cylinder diesel research engine at different engine loads, intake air pressures and EGR levels. Hydrogen was aspirated with the intake air, and EGR was simulated by supplying the intake pipe with compressed nitrogen gas. The results showed a reduction in CO2 and particulate emissions with increasing H2 addition, and an increase in NOx emissions at H2 levels greater than 10% of the total input energy to the engine. The next stage involved tests on a chassis dynamometer with a small van equipped with the multi-cylinder version of the single cylinder research engine. The van was fitted with a programmable H2 augmentation system, with H2 addition levels specified by accelerator pedal position. During full drive cycle tests conducted with and without H2 augmentation up to 10%, an average rate of 1 kW of H2 was supplied to the engine. With H2 augmentation, over the total drive-cycle, reductions in CO, NOx and particle number were observed, but a higher total PM mass was recorded. Highlights: Hydrogen-diesel co-combustion was conducted on single cylinder research engine. H2 was also supplied to a vehicle on a chassis dynamometer operated on drive cycle. H2 addition levels to the vehicle were specified by accelerator pedal position. For single cylinder engine, CO2 and particles reduced, while NOx varied with load. For vehicle, CO, NOx and particle number reduced, while total PM mass increased.